Basin Study in Atambua, West Timor, Indonesia from Gravity Data - Edy Wijanarko; Ilham Arisbaya; Prihadi Sumintadireja; Warsa Warsa; Hendra Grandis (Journal of Mathematical and Fundamental Sciences, 2022)
Timor Island, Indonesia has complex geological structures related to its tectonic history. There is an existing subsurface geological model that is based on geophysical data. It is limited to the regional crustal scale and has a relatively low spatial resolution. The objective of our study was to delineate the sedimentary basin configuration of the area, both laterally and vertically, based on gravity data. Spectral analysis of the Bouguer anomaly allowed for anomaly enhancement by wavenumber domain filtering. Two main basins were identified from elongated low gravity anomalies that follow a SW-NE trend, i.e., the Central Basin and the Atambua Basin. The 2½D gravity modeling of selected profiles perpendicular to the regional structural direction revealed the sedimentary fills of the basins and the basement based on their densities. The Bobonaro mélanges and Viqueque sequences dominate and overlay the syn-rift (Kekneno sequences) and post-rift (Kolbano sequences) with varying lithology. These para-autochthon sediments are dominated by shale and carbonaceous rocks. Their respective thicknesses and depths of burial imply the possibility of hydrocarbon generation. The underlying basement may be associated with the Australian crust protruding from the south.